2021
DOI: 10.3390/foods10112575
|View full text |Cite
|
Sign up to set email alerts
|

Chestnut Cultivar Identification through the Data Fusion of Sensory Quality and FT-NIR Spectral Data

Abstract: The world production of chestnuts has significantly grown in recent decades. Consumer attitudes, increasingly turned towards healthy foods, show a greater interest in chestnuts due to their health benefits. Consequently, it is important to develop reliable methods for the selection of high-quality products, both from a qualitative and sensory point of view. In this study, Castanea spp. fruits from Italy, namely Sweet chestnut cultivar and the Marrone cultivar, were evaluated by an official panel, and the respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Moreover, this technique has been widely used for the quality assessment of nuts. For example, a study conducted in 2021 [ 19 ] with sensory and qualitative analysis of chestnuts, used data fusion strategies, taking advantage of the synergistic effect of the information obtained from sensory analysis of chestnuts with the help of the panel and QDA test and the data obtained by NIR. This study showed that sweet chestnuts, due to their characteristics, have the potential to be used in secondary products such as jam and flour, as mentioned before.…”
Section: Methods and Sensory Lexicons Used On Chestnut Sensory And Qu...mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, this technique has been widely used for the quality assessment of nuts. For example, a study conducted in 2021 [ 19 ] with sensory and qualitative analysis of chestnuts, used data fusion strategies, taking advantage of the synergistic effect of the information obtained from sensory analysis of chestnuts with the help of the panel and QDA test and the data obtained by NIR. This study showed that sweet chestnuts, due to their characteristics, have the potential to be used in secondary products such as jam and flour, as mentioned before.…”
Section: Methods and Sensory Lexicons Used On Chestnut Sensory And Qu...mentioning
confidence: 99%
“…On the other hand, it is a rich source of starch (carbohydrates), protein, dietary fiber, vitamins, minerals (such as potassium, phosphorous, and magnesium), lipids, and nutrients. Furthermore, it is a good source of antioxidants such as L -ascorbic acid, carotenoids, and phenolic compounds such as gallic and ellagic acids [ 2 , 15 , 16 , 17 , 18 , 19 ]. Due to the mentioned characteristics, the chestnut may have beneficial health effects, arousing consumer interest.…”
Section: Chestnut Chemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“… [ 80 ] Environmental Evaluate the state of conversion over time for an ecosystem Conductivity; pH; NIR; Fluorescence emission-excitation data MLDF MCR-ALS PARAFAC; MCR-ALS / MLDF > individual model / [ 184 ] Quantify potentially toxic elements from soil NIR; TXRF LLDF; MLDF SVM UF; GA DF-individual model comparison response dependent; GA > UV e.d. [ 113 ] Food Chestnut cultivar identification Sensory evaluation; FT-NIR LLDF PLS-DA - DF-individual model comparison LLDF > individual model (response dependent) / [ 185 ] Authentication of raw and cooked free-dried rainbow trout fillets NIR; Colorimetry; Texture analysis LLDF PLS-DA; LDA; QDA; kNN - DF-individual model comparison LLDF > individual model e.d. [ 186 ] …”
Section: Table A1mentioning
confidence: 99%
“…The nut and kernel trait measurements were carried out using a digital caliper (Sigma-Aldrich, Germany) with an accuracy of 0.01 mm. The geometric mean diameter (Dg), sphericity (Φ) and volume (V) were calculated by using the following equations [25][26][27][28]: Dg = (LWT) 1/3 (1)…”
Section: Almond Samples and Experimentsmentioning
confidence: 99%